Dynamics of Islamic Communication Between National Political Parties and Local Political Parties in South Aceh and Southwest Aceh Districts Ahead of the 2024 Legislative Election - Irpannusir, Irpannusir; Katimin, Katimin; Nurhanifa, Nurhanifa (Faculty of Law, Universitas Pekalongan, 2024)
This study examines the dynamics of political communication between national political parties and local political parties in Southwest Aceh Regency (Kabupaten Aceh Barat Daya) and South Aceh Regency (Kabupaten Aceh Selatan) leading up to the 2024 Legislative Election. The research employs a qualitative methodology, which seeks to uncover issues, conditions, or events (fact-finding) experienced by the research subjects, including behaviors, perceptions, motivations, and actions holistically. These findings are then described in words and language within a specific natural context using various natural methods. The study aims to describe the dynamics of political communication between national and local political parties, analyze the implications of these dynamics, formulate the concept of Islamic political communication as a strategy to strengthen political communication between national and local parties, and identify barriers to implementing Islamic political communication as a strategy in Abdiya and South Aceh regencies leading up to the 2024 Legislative Election. The research findings reveal: First, the dynamics of political communication between national and local parties in Abdiya and South Aceh leading up to the 2024 Legislative Election are quite dynamic, characterized by the development of both effective and ineffective political communication. If not managed properly, ineffective political communication is likely to become dominant. Second, the implications of political communication between national and local parties in Abdiya and South Aceh leading up to the 2024 Legislative Election are also dynamic, with various forms of political messages impacting the audience and becoming targets for other political media/channels. There are three types of communication effects: cognitive, affective, and behavioral, all of which are significantly observed in Aceh Abdya and South Aceh. Third, Islamic political communication as a strategy to strengthen effective political communication by national and local parties in Abdiya and South Aceh leading up to the 2024 Legislative Election is seen as a suitable solution, although it requires a long process.